Pengembangan Potensi Wisata Tlogo Ploso dan Potensi Pertanian Tembakau di Kalurahan Giritirto, Kapanewon Purwosari, Kabupaten Gunungkidul - Nernere, Maria Setyaningsih (Jurnal Atma Inovasia, 2021)
Giritirto Village is a region that has many potentials especially in natural resources. One of the potentials from Giritirto Village is Tlogo Ploso with its various benefits. Besides as an irrigation sources, Tlogo Ploso has many potentials to develop. Another potential from Giritirto Village is their plantation products, especially tobacco plantations. Tobacco becomes one of the sources that can increase the public’s economy because it can be processed into several products. Besides being able to processed into cigarette, tobacco can also be processed into natural pepticides. It is expected that an exploration through literature study can be done in Giritirto potentials from the Tlogo Ploso and also creating alternatives for making products from tobacco as an raw material for making natural pepticide, so that can increase the quality of selling value and also ensure the economic condition of the people at the Giritirto Village so their economic condition can be better.